Home or Away? : Profit Shifting with Territorial Taxation - Langenmayr, Dominika (IMF Working Papers; Working Paper, 2022)
In 2009, the United Kingdom abolished the taxation of profits earned abroad and introduced a territorial tax system. Under the territorial system, firms have strong incentives to shift profits abroad. Using a difference-in-differences research design, we show that the profitability of UK subsidiaries in low-tax countries increased after the reform compared to subsidiaries of non-UK multinationals in the same countries by an average of 2 percentage points. This increase in profit shifting also leads to increases in measured productivity of the foreign affiliates of UK multinationals of between 5 and 9 percent.